The Subcontinent Falls Apart: Communal Violence and Religious Intolerance in Khushwant Singh’s Train to Pakistan - Abdullah, Md Abu Shahid (Literary Studies, 2021)
The aim of the article is to show the breakdown of trust and harmony among people from different religious and communal background caused by the partition as depicted in Khushwant Singh’s Train to Pakistan. The article also focuses on the way the novel criticises the indifference of men with power and authority, and the passivity and fear of social, political and religious leaders over the communal violence during and after the partition. Last but not the least, the article also highlights the way the novel portrays the love between a Sikh boy and a Muslim girl where the Sikh boy Juggut Singh sacrifices himself in order to save his beloved Nooran and consequently saves the life of thousands of Muslims targeted for massacre.